Collapse Behaviour Assessment of Precast Soft Storey Building. (2015) - Wibowo, Ari; Wilson, John L.; Lam, Nelson TK; Gad, Emad F
Abstract: Soft-storey buildings are considered to be particularly vulnerable because the rigid block formed by upper levels has limited energy absorption and displacement capacity, thus leaving the columns in the soft-storey to deflect and absorb the seismic energy whilst resisting the axial gravity loading. To investigate collapse mechanism of such structures, a unique experimental field testing of a precast soft storey building in Melbourne was then undertaken. Four pull-over tests were conducted to measure the drift capacity and load-deflection behaviour of such buildings. Detailed theoretical models were developed that considered rocking behaviour, connection behaviour, P-Delta effects and ground slab interaction effects. The experimental results together with a comparison with theoretical model predictions showed that the precast soft storey structure had considerable displacement capacity beyond the traditional definition of failure used in high seismic regions, where failure is deemed to occur when the horizontal resistance capacity of the system is reduced to 80% of the nominal capacity. It is recommended that the nominal failure point could be reduced to a displacement limit set at the lesser of the displacement associated with 40% of the peak strength or 60% of the column width to allow for some conservatism. This preliminary definition is considered more realistic, particularly for regions of lower seismicity where the ground shaking is more modest in terms of displacement demand and duration and P-delta effects are not as significant.